2022
DOI: 10.3389/frobt.2022.858893
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Upper-Limb Exoskeletons Designed for Use in the Working Environment—A Literature Review

Abstract: Introduction: Many employees report high physical strain from overhead work and resulting musculoskeletal disorders. The consequences of these conditions extend far beyond everyday working life and can severely limit the quality of life of those affected. One solution to this problem may be the use of upper-limb exoskeletons, which are supposed to relieve the shoulder joint in particular. The aim of this literature review was to provide an overview of the use and efficacy of exoskeletons for upper extremities … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 56 publications
0
18
0
Order By: Relevance
“…Further, the target population for exoskeletons in general is very heterogeneous. Research on exoskeletons is primarily carried out in the medical field [ 104 ], in addition to military use or use in the working environment [ 105 ]. Here, the focus is on diseases that severely restrict movement, such as stroke or paraplegia.…”
Section: Discussionmentioning
confidence: 99%
“…Further, the target population for exoskeletons in general is very heterogeneous. Research on exoskeletons is primarily carried out in the medical field [ 104 ], in addition to military use or use in the working environment [ 105 ]. Here, the focus is on diseases that severely restrict movement, such as stroke or paraplegia.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the potential of PSEs (de Looze et al, 2016), and their experimentally confirmed ability to reduce joint load, muscle activity and muscle fatigue during laboratory based overhead work (De Vries and De Looze, 2019;Bär et al, 2021;De Bock et al, 2022a;van der Have et al, 2022), large-scale adoption in industry is not yet forthcoming (Crea et al, 2021). This may partially be explained by the limited representativeness of laboratory studies Moeller et al, 2022) and the lack of generalizability of field studies (Crea et al, 2021;De Bock et al, 2022b;Kuber et al, 2022). Furthermore, effort expectancy, social influence, and performance expectancy determine the intention to use exoskeletons prior to testing an exoskeleton (Elprama et al, 2020), and perceived comfort, task-technology fit, perceived safety, and perceived usefulness affect the intention to use an exoskeleton after testing the device (Schwerha et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Even though the potential positive effects of PSEs on employees' health might be significant (de Looze et al, 2016;Moeller et al, 2022), some concerns towards precision performance remain. Overhead work endurance performance increases when wearing a PSE (Butler, 2016;Spada et al, 2017), which is confirmed by reductions in muscle activity and fatigue (De Vries and De Looze, 2019;Bär et al, 2021;De Bock et al, 2022a;Schmalz et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Active systems (e.g., shoulder exoskeleton S700 (exoIQ, Hamburg, Germany)), on the other hand, have the potential to regulate the support level during the use itself, adapting to the requirement of the manual task and individual wishes. Many studies have shown the effect of load reduction on workers with an exoskeleton [6][7][8]. Otten et al showed a possible reduction in shoulder muscle activity of up to 58.2% with the Lucy exoskeleton during overhead activities [9,10].…”
Section: Introductionmentioning
confidence: 99%